2019
DOI: 10.1182/bloodadvances.2019000025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients with relapsed/refractory B-cell non-Hodgkin lymphoma treated with blinatumomab

Abstract: Blinatumomab, the first-in-class CD3/CD19 bispecific T-cell engager antibody construct, has recently been approved for treating patients with relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia. However, the clinical proof of concept of blinatumomab efficacy was initially demonstrated in patients with R/R B-cell non-Hodgkin lymphoma (B-NHL) in the MT103-104 phase 1 dose-escalation and expansion trial (NCT00274742), which defined 60 µg/m2 per day as the maximum tolerated dose (MTD). The clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…Bispecific T-cell engager (BiTE ® ) molecules are a clinically validated therapeutic modality that redirect a patient's T cells to kill tumor cells (15). Blinatumomab, the first BiTE ® molecule in clinical development, is approved for the treatment of relapsed/refractory B-cell precursor acute lymphoblastic leukemia (16)(17)(18) and also demonstrates efficacy in non-Hodgkin lymphoma (19)(20)(21). The BiTE ® molecule AMG 420, which targets BCMA, demonstrated a 70% response rate in multiple myeloma with 50% minimal residual disease-negative complete responses at the maximum tolerated dose in a phase 1 study (22).…”
Section: Introductionmentioning
confidence: 99%
“…Bispecific T-cell engager (BiTE ® ) molecules are a clinically validated therapeutic modality that redirect a patient's T cells to kill tumor cells (15). Blinatumomab, the first BiTE ® molecule in clinical development, is approved for the treatment of relapsed/refractory B-cell precursor acute lymphoblastic leukemia (16)(17)(18) and also demonstrates efficacy in non-Hodgkin lymphoma (19)(20)(21). The BiTE ® molecule AMG 420, which targets BCMA, demonstrated a 70% response rate in multiple myeloma with 50% minimal residual disease-negative complete responses at the maximum tolerated dose in a phase 1 study (22).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 3 patients in phase 2 R/R DLBCL study achieved late CRs that were not captured in this pooled analysis and had longer DOCRs [5]. Furthermore, in a subset of patients with R/R B-NHL from phase 1 study (NCT00274742), remission is ongoing after more than 7 years [10]. There was no difference between CR and non-CR patients in rate of prior transplant or double hit disease.…”
mentioning
confidence: 83%
“…The most advanced BiTe in clinical development for B cell malignancies is blinatumomab, an antibody that crosslinks B cells and T cells by ligating CD3 and CD19. In phase I trial of relapsed/refractory NHL (n = 76), blinatumomab demonstrated an ORR of 69% and a CR rate of 37% [95] with durable responses in some patients on long-term follow-up [96]. Of note, patients with relapsed/refractory MCL (n = 24) had a higher ORR compared to DLBCL (71% versus 55%, respectively) [95].…”
Section: Bite Antibodiesmentioning
confidence: 98%